Parametric excitation of stay-cables - Gani, Ferawati (University of Ottawa (Canada), 2004)
The main objective of this thesis is to develop a finite-element-based cable model to study a self-excited phenomenon categorized as "the parametric excitation" of stay-cables, particularly for the cable-stayed bridges. Non-linear numerical methods were adopted and implemented in Matlab programming. When linearized, the cable model can be utilized to obtain the 3D natural frequencies and corresponding mode-shapes. Using the methodically developed numerical approach, this study was able to realize the existence of parametric excitation of cables under certain conditions and parameters. As more insightful analyses performed, more interesting results were gained, such as the existence of bifurcation and chaotic vibration of cable systems. The thesis found many possibilities of parametric excitation that stay-cables may encounter. Further study on the topic of parametric excitation of stay-cables is definitely important and there is also a need to extend the study by including the field measurement.
Keywords: Engineering, Civil.